Model Pembelajaran Respons Verbal dalam Kemampuan Berbicara - Nurlaelah Nurlaelah; Geminastiti Sakkir (Universitas Muhammadiyah Enrekang, 2020)
The purpose of this study is to find out the effect of the implementation of verbal response learning model to the speaking ability students of Class X Madrasah Aliyah PP DDI As-Salman Allakuang Sidenreng Rappang Regency. This research was conducted in Madrasah Aliyah PP DDI As-Salman Allakuang Sidenreng Rappang Regency. The research method used quantitative method. The subject of the research is the students of class X Madrasah Aliyah PP DDI As-Salman Allakuang Sidenreng Rappang Regency academic year 2016/2017. The data collection technique used a test with two stages of data retrieval, the first test to determine the speaking ability before the students were given treatment (pretest) and the second stage to determine students' speaking ability after being given treatment (posttest). Results based on db of 52 converted to t-table at the 5% significance level obtained the price of 1.671. Criteria of submission are if t-test ≥ t-tabel then Ha accepted and Ho rejected, otherwise if t-test ≤ t-table then Ha rejected and Ho accepted. It turns out that t-test is magnitude 2.33 more than t-table, hence alternative hypothesis accepted and null hypothesis rejected. Based on these results it can be concluded that the application of verbal response learning model significantly affects the speaking ability of grade X Madrasah Aliyah PP DDI As-Salman Allakuang of Sidenreng Rappang Regency.